2017
DOI: 10.4184/asj.2017.11.5.787
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Evaluation of Respiratory Muscle Strength after Scoliosis Correction in Patients with Duchenne Muscular Dystrophy

Abstract: Study DesignRetrospective cohort study.PurposeTo investigate the effect of spinal correction on respiratory muscle strength in patients with Duchenne muscular dystrophy (DMD).Overview of LiteratureSeveral studies have reported that scoliosis correction in patients with DMD does not improve pulmonary function. In these studies, pulmonary function was evaluated using the traditional spirometric values of percent vital capacity (%VC) and percent forced vital capacity (%FVC). However, traditional spirometry may no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
(56 reference statements)
1
11
0
Order By: Relevance
“…Accurate predicted values for nonambulatory patients with severe weakness and scoliosis are difficult due to error introduced by methods of height estimation when standing height cannot be measured. Our results are similar to the findings of Saito et al 5 in Duchenne muscular dystrophy who found no improvement in vital capacity postscoliosis surgery, with their data suggesting a trend (not statistically significant) toward decreased vital capacity. Our results contrast with Saito et al who suggested a small improvement in respiratory strength; we found no statistically significant nor clinically important change in respiratory strength measures comparing before and after scoliosis surgery.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Accurate predicted values for nonambulatory patients with severe weakness and scoliosis are difficult due to error introduced by methods of height estimation when standing height cannot be measured. Our results are similar to the findings of Saito et al 5 in Duchenne muscular dystrophy who found no improvement in vital capacity postscoliosis surgery, with their data suggesting a trend (not statistically significant) toward decreased vital capacity. Our results contrast with Saito et al who suggested a small improvement in respiratory strength; we found no statistically significant nor clinically important change in respiratory strength measures comparing before and after scoliosis surgery.…”
Section: Discussionsupporting
confidence: 92%
“…4 A study of 16 patients with Duchenne muscular dystrophy found no improvement in forced vital capacity comparing pre-to postoperative values. 5 A study of 10 patients with spinal muscular atrophy found no significant differences in forced vital capacity comparing before and after scoliosis surgery, although 6 of 10 had a small improvement (mean, 0.2 L; SD, 0.1 L) in forced vital capacity atone to 4 years follow up. 6 A retrospective chart review study, published in 1995, of patients with spinal muscular atrophy found that among nine patients who had vital capacity measured before and after scoliosis surgery, eight (89%) had an increase in vital capacity, while one had a decrease in vital capacity on 5 to 76 months (mean, 39 months) follow up.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Saito retrospectively reviewed lung function and respiratory muscle strength preoperatively, 1 month and 6 months postoperatively in 16 patients with DMD. Although no significant difference was observed in FVC and VC, mean values of PI max and PE max significantly improved postoperatively 16 .…”
Section: Discussionmentioning
confidence: 61%
“…The rate of decline in LFT results had broad confidence intervals due to small sample, which possible explains the non-significant mean change in progression rate. However, compared to other studies we included more patients 1,2,8,[11][12][13]16 . The follow up time of our study was limited.…”
Section: Discussionmentioning
confidence: 99%